Pengaruh Kemampuan Manajerial Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru di SMP Rujukan Se-Kabupaten Magetan - Esti Nurhayati; Murtadlo Murtadlo; Erny Roesminingsih; Amrozi Khamidi; Kaniati Amalia (LP. Ma'arif Janggan Magetan, 2024)
The influence of principal's managerial ability and work motivation on teacher performance in referral junior high schools throughout Magetan Regency aims to: 1) Analyze the influence of principal's managerial ability on teacher performance. 2) Analyze the influence of work motivation on teacher performance. 3) Analyze the influence of principal managerial ability and work motivation simultaneously on teacher performance. The research is a correlational research type and was conducted quantitatively. The research population was 104 with a sample of 10 people. Data collection using questionnaires. Data analysis techniques with data descriptions, classic assumption tests include normality tests, heteroscedasticity tests, multicollinearity tests, and linearity tests. The results of this study are: 1) Principal's managerial ability has a significant effect on teacher performance (t-test= 0.194). 2) Work motivation has a significant effect on teacher performance (t-test=0.677). 3) The principal's managerial ability and work motivation have a significant effect on teacher performance (f-test=0.000 <0.05). The conclusion of this study is that the principal's managerial ability and work motivation have an effect on teacher performance (f-test=73.570 with a significance of 0.000). Principals are suggested to improve their managerial skills by attending leadership and educational management training. Teachers are expected to improve their work motivation by developing themselves through professional training, seminars, and workshops that are relevant to their duties